Impaired Brain Energy Metabolism: Involvement in Depression and Hypothyroidism - Głombik, Katarzyna; Detka, Jan; Kurek, Anna; Budziszewska, Bogusława (Frontiers in Neuroscience, 2020)
Although hypothyroidism appears to be an important factor in the pathogenesis of depression, the impact of thyroid hormones on the bioenergetics of the adult brain is still poorly known. Since metabolic changes are reported to be a key player in the manifestation of depressive disorder, we investigated whether there are differences in selected metabolic markers in the frontal cortex and hippocampus of Wistar Kyoto rats (WKY; an animal model of depression) compared to those of control Wistar rats and whether the induction of hypothyroidism by propylthiouracil (PTU) elicits similar effects in these animals or intensifies some parameters in the WKY rats. In our study, we used WKY rats as a model of depression since this strain exhibits lower levels of monoamines in the brain than control rats and exhibits behavioral and hormonal alterations resembling those of depression, including increased reactivity to stress. The findings indicate a decrease in glycolysis intensity in both brain structures in the WKY rats as well as in both strains under hypothyroidism conditions. Furthermore, hypothyroidism disrupted the connection between glycolysis and the Krebs cycle in the frontal cortex and hippocampus in the depression model used in this study. Decreased thyroid hormone action was also shown to attenuate oxidative phosphorylation, and this change was greater in the WKY rats. Our results suggest that both the depression and hypothyroidism models are characterized by similar impairments in brain energy metabolism and mitochondrial function and, additionally, that the co-occurrence of hypothyroidism and depression may exacerbate some of the metabolic changes observed in depression.